Pengaruh Non Debt Tax Shield, Effective Tax Rate, dan Asset Tangibility terhadap Struktur Modal pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Galih Hardika; Ahmad Yani; Beby Hilda Agustin (Jurnal Riset Akuntansi, 2026)
This study aims to analyze the effect of Non-Debt Tax Shield (NDTS), Effective Tax Rate (ETR), and Asset Tangibility on the capital structure of property and real estate companies listed on the Indonesia Stock Exchange during the 2021–2025 period. The property and real estate sector was selected due to its characteristics of requiring substantial capital investment and possessing high-value assets that can be used as collateral for debt financing. This research employed a quantitative descriptive approach with purposive sampling as the sampling technique. Data analysis was conducted using multiple linear regression to examine the partial and simultaneous effects of the independent variables on capital structure. The results indicate that Non-Debt Tax Shield (NDTS) has a negative and significant effect on capital structure, while Effective Tax Rate (ETR) and Asset Tangibility have a positive and significant effect on capital structure. Simultaneously, NDTS, ETR, and Asset Tangibility significantly influence the capital structure of property and real estate companies. These findings suggest that tangible assets and tax protection strategies are major considerations in determining corporate financing decisions through debt. The implications of this study indicate that companies need to optimize the management of tangible assets and tax efficiency in formulating capital structure policies, while investors may use this information as an important consideration in evaluating corporate financing decisions.